Psychological Changes and Cancer Occurrence in Seoul Citizens Due to Changes in Fine Dust Concentration before Seoul Fine Dust Policy - Kilyong Choi (MDPI AG, 2021)
Background: Particulate matter and urban air pollution affect the human body and can lead to death. Epidemiological studies should consider exposure to pollutants and the diverse responses of individuals, depending on their sensitivity to the pollutants. Methods: In this study, air pollution measurements were obtained hourly at measuring stations operated by national and local governments to increase the reliability of the measured values. A β-ray absorption method was used to analyze the measurements of fine dust and determine the particulate matter content. Results: The air pollution data were log-linear, thereby enabling a comparison of data from different time periods. The comparison was made by focusing on the period of the implementation of Seoul’s fine dust policy. It was observed that the cancer incidence rate decreased after the implementation of the policy. The data on individual characteristics were obtained from a survey of Seoul citizens conducted from 2015 to 2016 using indicators such as quality of life and the social trust of Seoul citizens. Conclusion: The survey on the living environment and residence indicated that 80% of the heads of households were men. Women had a greater dissatisfaction than men with their residential, economic, and social environments. The survey questions on well-being were related to elements of internal and external environments, such as air pollution, noise, and fine dust.